RANCANG BANGUN PURWARUPA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) 20 WP DENGAN DUAL AXIS SOLAR TRACKING BERBASIS IOT UNTUK BUDIDAYA JAMUR - Sukadana, I Putu Gede; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
Oyster mushrooms (Pleurotus ostreatus) are horticultural commodities with high economic value and stable market demand. However, in the cultivation process, environmental factors such as temperature and humidity in the mushroom house need to be controlled to ensure optimal mushroom growth. One solution to improve efficiency and sustainability in oyster mushroom cultivation is the use of renewable energy, such as Solar Power Plants (PLTS). The efficiency of PLTS highly depends on the intensity and position of sunlight received by the solar panels, making the use of a solar tracking system essential.This study aims to design and test a 20 WP PLTS prototype based on Dual Axis Solar Tracking with Internet of Things (IoT) technology. The research results show that the maximum power output reached 21 watts at 14:00 WITA. Additionally, the prototype was able to generate 127.6 Watt Hours (WH) of energy under clear weather conditions during a 9-hour testing period. With the implementation of IoT technology, this system can operate automatically. The implementation of the 20 WP PLTS based on Dual Axis Solar Tracking can be a solution to support modern agriculture by utilizing renewable energy and reducing dependence on conventional electricity.